How Much Deformity Correction and Maintenance Can We Obtain by LLIF and will it be Affected by Approach Side or Levels?. Issue 1 (April 2016) - Cho, Woojin
Introduction: Lateral lumbar interbody fusion (LLIF) is one of the minimally invasive surgeries that have shown the successful surgical outcome. The purpose of this study is to report the amount of deformity correction achieved with LLIF, and to compare the effect of convex versus concave approach side on the magnitude of correction. Methods: Out of 512 LLIF cases, 100 stand-alone LLIF cases for degenerative lumbar scoliosis were identified after excluding previous fusion, posterior fixation, and cases without scoliosis. Radiographic and clinical data were analyzed retrospectively. In each patient, overall and segmental deformity correction (difference between postop and preop) and maintenance (difference between final and postop) were measured, and the amount of segmental correction and maintenance was compared in terms of approach side (convex versus concave). Also, correction was compared between groups with or without end plate fracture, and maintenance was compared between the groups with or without subsidence. Results: Total 34 patients with follow up were included, and a total of 86 levels were treated. The amount of overall and segmental correction and maintenance is illustrated inTable 1 . Overall and segmental scoliosis correction was more predictable than lordosis creation. The upper levels had the tendency of more segmental scoliosis correction, but not significant. There was no difference in the amount of segmental correction and maintenance in between convex and concave side. The group without the endplate fracture showed more segmental scoliosis correction significantly, the group without the subsidence showed more segmental scoliosis and lordosis maintenance significantly. Conclusion: We report the amount of overall and segmental deformity correction and maintenance by LLIF procedure. Segmental scoliosis correction is very predictable unless endplate breakage occurs during surgery. Segmental deformity correction maintained well until final follow up unless subsidence occurs. Overall or Segmental lordosis creation is less predictable as we proposed it is dictated by the position of the cage. There was no difference in the amount of segmental correction and maintenance in between convex and concave side. Table 1 Sample identification Fig. 1